Pengaruh Partisipasi Anggota Terhadap Keberhasilan Koperasi Serba Usaha di Kota Denpasar - Sugiastini, Ida Ayu Febry; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 3, Maret 2015 (pp. 139 - 219), 2015)
This study aimed to determine the effect of democracy members, capital, and utilization of services simultaneously and partially on the success of the business cooperatives in Denpasar. In addition it was also discussed about the dominant factor affecting the success of business cooperatives in the city of Denpasar. This study used a method of analysis that combines factor analysis and regression analysis. Factor analysis is done to obtain a score factor based on the latent variables are formed by the indicator variable, while the regression analysis was conducted to determine the effect of independent variables on the dependent variable. The analysis showed that both simultaneously and partially democratic members, capitalization, and service utilization significantly influence the success of business cooperatives in Denpasar. Analysis of the factors examined in the study showed that the variables dominant influence on the success of business cooperatives in Denpasar is variable service utilization.
Keywords: democracy members; capitalization; service utilization; the success of the cooperative